Politics, society, and colonialism an alternative understanding of Tagore's responses - Mukhopadhyay, Amartya (Foundation Books, 2010)
Even as his 150th birth anniversary draws near, Rabindranath Tagore remains quite under-explored. Nirad C. Chaudhuri predicted that the difficulty in translating Tagores work would ascertain that in future his work will lie like a buried city in the past. The difficulty of translating him in any of the European or modern Indian languages and his position as a cult figure in India contributed to this gap between adulation and understanding. Recent revival of interest in the West in Tagores work only partly redresses this imbalance. For, much of Tagores central claim to greatness lies in his social thought